2003
DOI: 10.1083/jcb.200211091
|View full text |Cite
|
Sign up to set email alerts
|

uPARAP/Endo180 is essential for cellular uptake of collagen and promotes fibroblast collagen adhesion

Abstract: The uptake and lysosomal degradation of collagen by fibroblasts constitute a major pathway in the turnover of connective tissue. However, the molecular mechanisms governing this pathway are poorly understood. Here, we show that the urokinase plasminogen activator receptor–associated protein (uPARAP)/Endo180, a novel mesenchymally expressed member of the macrophage mannose receptor family of endocytic receptors, is a key player in this process. Fibroblasts from mice with a targeted deletion in the uPARAP/Endo18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
220
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(234 citation statements)
references
References 29 publications
13
220
0
1
Order By: Relevance
“…The importance of CTLD4 for the formation of the suppressive Endo180-CD147 complex in PECs was not uncovered in Endo180 DEx2-6/DEx2-6 mice that express a truncated form of the Endo180 receptor, including an intact CTLD4, and reach adulthood (32,33). Nevertheless, our analysis of prostate tissue from adult Endo180 DEx2-6/DEx2-6 mice has revealed that a significant architectural change occurs that closely recapitulates prostatic intraepithelial neoplasia, a common precursor for invasive prostate cancer (M. Rodriguez-Teja and colleagues; unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of CTLD4 for the formation of the suppressive Endo180-CD147 complex in PECs was not uncovered in Endo180 DEx2-6/DEx2-6 mice that express a truncated form of the Endo180 receptor, including an intact CTLD4, and reach adulthood (32,33). Nevertheless, our analysis of prostate tissue from adult Endo180 DEx2-6/DEx2-6 mice has revealed that a significant architectural change occurs that closely recapitulates prostatic intraepithelial neoplasia, a common precursor for invasive prostate cancer (M. Rodriguez-Teja and colleagues; unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Members belonging to the macrophage mannose receptor protein family may be possible candidates because they have been shown to internalize some LRP-1 ligands and play a crucial role in ECM turnover. For instance, urokinase plasminogen activator receptor-associated protein/endocytic recycling protein Endo180 is expressed in chondrocytes and fibroblasts and is involved in collagen internalization (40,41). TIMP-1 and TIMP-2 are also endocytosed by LRP-1 (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between various collagen types and Endo180 appears to play a role in cell-matrix adhesion, since Endo180-deficient cells have a 50% reduction in adhesion to type V collagen and also a reduced ability to bind to purified types I and IV collagen (54). To investigate whether the C-terminal glycine repeat region and C-prodomain of the ␣1 chain collagen mediate this adhesion to Endo180, we performed competition binding experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The four receptors are type I transmembrane proteins with a highly conserved structure composed of an N-terminal cysteine-rich or ricin-type domain, a fibronectin type II domain, 8 or 10 C-type lectin-like domains (CTLDs), a single transmembrane domain, and a short cytoplasmic domain (51). Endo180 previously has been shown to act as a collagen receptor by binding to gelatin, type I, type II, type IV, and type V collagens and also mediates endocytosis and turnover of these extracellular matrix proteins (52)(53)(54)(55)(56). The fibronectin type II domain of Endo180 (which shares a highly conserved sequence with other collagen-binding fibronectin type II domains, such as fibronectin, MMP-2, and MMP-9 (49, 51, 52)) appears to be required for binding to these collagens.…”
Section: Discussionmentioning
confidence: 99%